Scoping out noisy galvanic vestibular stimulation: a review of the parameters used to improve postural control - McLaren, Ruth; Smith, Paul F.; Taylor, Rachael L.; Niazi, Imran Khan; Taylor, Denise (Frontiers in Neuroscience, 2023)
Objective: Noisy galvanic vestibular stimulation (nGVS) has been used to facilitate vestibular function and improve gait and balance in people with poor postural control. The aim of this scoping review is to collate, summarise and report on the nGVS parameters that have been used to augment postural control. Method: A systematic scoping review was conducted up to December 2022, following the method described by Arksey and O’Malley (2005). Data were extracted and synthesised from 31 eligible studies. Key nGVS parameters were identified, and the importance of these parameters and their influence on postural control evaluated. Results: A range of nGVS parameters have been used to augment postural control, including; noise waveform, amplitude, frequency, duration of stimulation, method of amplitude optimisation, size and composition of electrodes and the electrode skin interface. Conclusions: Systematic evaluation of the individual parameters that can be manipulated in the nGVS waveform identified that a broad array of settings have been utilized in each parameter across the studies. Choices made around the electrode and electrode-skin interface, as well as the amplitude, frequency, duration and timing of the waveform are likely to influence the efficacy of nGVS. The ability to draw robust conclusions, about the selection of optimal nGVS parameters to improve postural control is hindered by a lack of studies that directly compare parameter settings or consider the variability in individuals' response to nGVS. We propose a guideline for the accurate reporting of nGVS parameters, as a first step towards establishing standardized stimulation protocols.